The phenotype and function of murine bone marrow-derived dendritic cells is not affected by the absence of VDR or its ability to bind 1α, 25-dihydroxyvitamin D3. Issue 164 (November 2016) - Vanherwegen, An-Sofie; Ferreira, Gabriela Bomfim; Smeets, Elien; Yamamoto, Yoko; Kato, Shigeaki; Overbergh, Lut; Gysemans, Conny; Mathieu, Chantal
Highlights: A truncated VDR does not interfere with myeloid dendritic cell phenotype or function. Rendering VDR unable to bind ligand does not alter the phenotype of bone marrow-derived myeloid dendritic cells. An unliganded VDR does not affect the T cell stimulatory capacity of bone marrow-derived myeloid dendritic cells. Abstract: The nuclear vitamin D receptor (VDR) is generally recognized as a ligand-dependent transcription factor that mediates the actions of its natural ligand, 1α, 25-dihydroxyvitamin D3 (1α, 25(OH)2 D3 ) on multiple target genes involved in mineral homeostasis, bone development, as well as immune reactivity. As the VDR is widely distributed in nearly all cells of the body, it implies that the vitamin D endocrine system may regulate many cell types and functions. Experiments in VDR null mice established that the VDR has intrinsically critical roles in skin and keratinocyte biology but not in immune responses. Oppositely, absence of the VDR ligand is linked to susceptibility to autoimmunity, illustrating a potential role for the unliganded VDR in the immune system. This discrepancy stimulated us to further investigate the impact of the VDR on the phenotype and function of myeloid dendritic cells (DCs) generated ex vivo from bone marrow precursors of VDR null (with a truncated VDR) and VDR ΔAF2 mice (with a mutated C-terminal activation factor 2 domain thus rendering ligand-induced gene transcription impossible). Absent or unliganded VDR did not affect bone marrow-derived myeloid DC generation. DCs obtained from VDR null and VDR ΔAF2 bone marrow cells had comparable MHC-II, and costimulatory molecule CD86, CD80 and CD40 expression than DCs from wild-type bone marrow cells. Additionally, an unliganded VDR did not affect the cytokine production nor the antigen-specific T cell stimulatory capacity of bone marrow-derived DCs. In conclusion, we showed that although clear effects of 1α, 25-dihydroxyvitamin D3 are described on DC generation, absence of VDR or presence of an unliganded VDR does not affect the profile and function of ex vivo generated bone marrow-derived DCs.